2013
DOI: 10.1016/j.devcel.2013.04.021
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo Effector Yorkie Controls Normal Tissue Growth by Antagonizing Scalloped-Mediated Default Repression

Abstract: The Hippo tumor suppressor pathway restricts tissue growth by inactivating the transcriptional coactivator Yki. Although Sd has been implicated as a DNA-binding transcription factor partner for Yki and can genetically account for gain-of-function Yki phenotypes, how Yki regulates normal tissue growth remains a long-standing puzzle since Sd, unlike Yki, is dispensable for normal growth in most Drosophila tissues. Here we show that the yki mutant phenotypes in multiple developmental contexts are rescued by inact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
270
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 244 publications
(300 citation statements)
references
References 42 publications
17
270
1
Order By: Relevance
“…As shown in Figure 3G-3H, like Tgi, overxpression of Vg disrupted the interaction of Yki with Sd in a dose-dependent manner. We noted that, while it indeed impaired the interaction of Tgi with Sd ( Figure 3I) [24], overexpression of Yki failed to disrupt the Vg-Sd interaction under our experimental conditions (Supplementary information, Figure S3D), suggesting that Yki primarily competes with Tgi to bind Sd. We next performed further genetic tests, and found that EC-specific tgi knockdown suppressed the tumorous germarium phenotype induced by overexpression of Vg in ECs ( Figure 3J-3K).…”
Section: The Tondu-domain-containing Proteins Suppress Germ Cell Diffmentioning
confidence: 71%
See 4 more Smart Citations
“…As shown in Figure 3G-3H, like Tgi, overxpression of Vg disrupted the interaction of Yki with Sd in a dose-dependent manner. We noted that, while it indeed impaired the interaction of Tgi with Sd ( Figure 3I) [24], overexpression of Yki failed to disrupt the Vg-Sd interaction under our experimental conditions (Supplementary information, Figure S3D), suggesting that Yki primarily competes with Tgi to bind Sd. We next performed further genetic tests, and found that EC-specific tgi knockdown suppressed the tumorous germarium phenotype induced by overexpression of Vg in ECs ( Figure 3J-3K).…”
Section: The Tondu-domain-containing Proteins Suppress Germ Cell Diffmentioning
confidence: 71%
“…Given the recently proposed default repression model [24], we tested whether depletion of sd could reverse yki knockdown-induced tumorous germarium phenotype, and found that it indeed did ( Figure 2D-2E). Notably, we found that while yki knockdown in ECs caused female sterility, yki and sd double-knockdown females were fertile and exhibited normal germline development (Supplementary information, Figure S2B-S2C).…”
Section: Yki Maintains Ec Function Through the Canonical Hippo Pathwaymentioning
confidence: 92%
See 3 more Smart Citations